APPLICATION OF THE COMPLEX APPROACH FOR USAGE OF MUSIC COMPOSING SOFTWARE - Вишнівський, О. В. (Science-based technologies, 2019)
A complex approach of using the electronic composer has been proposed. Today, the scientific community has shown great interest in the problems of studying the interrelationships of music, mathematics and psychology. Therefore, creation and giving recommendations on the practical use of musical biotechnical automated control system, which allows to compose monophonic and polyphonic sound series using a stochastic basis or a regular random signal with a uniform distribution, with an objective to further application of this sound series for musical or musicaltherapeutic effects on the object of influence — cognitive functions of the human brain (aviation dispatcher, pilot, cosmonaut, etc.), has been considered. The modernized concept of automated music synthesis is highlighted, taking into account the requirements of both the quality of composed music and a significant reduction of the composer’s routine work. Such a strategy seems to be optimal today, or at least very promising. Automated music creation is one of the most difficult tasks in both applied mathematics and the development of targeted software. Within the framework of the proposed integrated approach, an exposition of a musical piece together with a cadenza is composed by the author of a musical work manually, while its polyphonic development is carried out with the help of the music composing software. The use of random numbers or a stochastic basis in a musical composition makes it possible to get a musical signal that is original in structure but somewhat monotonous in sound. To make it more sophisticated and eliminate the triviality of the musical texture, which is a consequence of the automation of the music composition process, a digital filter based on solution of a linear differential equation in fractional derivatives (according to Caputo) is used as the activation function of the neural scheme. The result of semi-automated modeling of the system is estimated as more natural, correct and strategically perspective.